The path planning for mobile robot based on bat algorithm. (1st January 2015) - Guo, Jinchao; Gao, Yu; Cui, Guangzhao
This article presents a novel method of global optimal path planning based on the Dijkstra algorithm and bat algorithm. This method consists of three steps: the first step is establishing the working space of mobile robot by adopting the MAKLINK graph theory, the second step is utilising the Dijkstra algorithm to obtain the sub–optimal path from the start point to the goal point, and the third step is adopting the bat algorithm to optimise the sub–optimal path so as to get the global optimal path of the robot. The result of the simulation experiment shows the proposed method is effective and can meet the real–time requirements of mobile robot. At the same time, the experiment also proves the optimal path planning of mobile robot based on bat algorithm is superior to particle swarm optimisation algorithm.